A comparison of the sensitivity of immunofluorescence and Giemsa for staining Chlamydia trachomatis inclusions in cycloheximide-treated McCoy cells. Issue 2 (February 1980) - Munday, P E; Johnson, A P; Thomas, B J; Taylor-Robinson, D
Abstract : In a clinical study of 190 men with non-gonococcal urethritis, Chlamydia trachomatis inclusions were sought in cycloheximide-treated McCoy cells by an indirect immunofluorescent antibody technique. The method was consistently reliable over a period of two years, and the results were obtained within 24 hours of a patient's attendance. The results correlated with those obtained by Giemsa staining in 91.6% of patients, and the new method was at least as sensitive as the established Giemsa-staining method.